EFFECTS OF FLOW REGULATION AND NON‐NATIVE SPECIES ON FEEDING HABITS OF EURASIAN OTTER Lutra lutra IN MEDITERRANEAN TEMPORARY RIVERS. (4th February 2014) - Bueno‐Enciso, J.; Díaz‐Ruiz, F.; Almeida, D.; Ferreras, P.
ABSTRACT In Mediterranean temporary rivers, ecological resources greatly fluctuate because of the high hydrological variability throughout the year. However, flow regulation prevents this natural regime and commonly entails associated non‐native species, which change the structure of aquatic communities. Nonetheless, few studies have tested the interaction of these two disruptive factors (flow regulation and non‐native species) and their synergistic effects on the Eurasian otter (Lutra lutra) diet at the river scale. The aim of this study was to compare the seasonal feeding habits of the otter between a temporary non‐regulated stretch and two regulated stretches invaded by non‐native species in a Mediterranean water course. The Bullaque River (Guadiana River Basin, central Spain) was seasonally sampled for otter spraints and prey abundance assessed from December 2009 to November 2010. Three stretches were considered: high (source, non‐regulated), medium (transition, regulated) and low (confluence, regulated). Diet varied from native prey in the high stretch (amphibians, insects and endemic cyprinids) to non‐native species in the low stretch (red‐swamp crayfish Procambarus clarkii and pumpkinseed sunfish Lepomis gibbosus). Seasonally, ingested biomass of native prey increased in spring. Diet was more diverse in the high stretch. Otters neutrally selected native cyprinids in the high stretch throughout the year, whereas crayfish was selected in the other two stretches. Overall results showed that flow regulation and non‐native species have increased prey availability for the otter; however, this paper highlights the importance of maintaining natural regimes in Mediterranean temporary rivers to conserve native communities and thus minimally impact food webs in Iberian freshwaters. Copyright © 2014 John Wiley & Sons, Ltd.